Karakterisasi Kompleks Inklusi Ketokonazol-Β-Siklodekstrin Menggunakan Metode Co-Grinding Berdasarkan Variasi Mol - Yeni Novita Sari; Syofyan Syofyan; Yella Matagi (Jurnal Farmasi Higea, 2015)
The research about characterization inclusion complex of ketoconazole-β-cyclodextrin with co-grinding method, with variations 1:1, 1:2,5 and 1:3 has been done. The formed inclusion complexes characterized by x-ray diffraction, IR spectrofotometer, scanning electron microscope and dissolution test. Dissolution test done based on Indonesian Pharmacopeia V Edition using apparatus type 2. The result of research showed that x-ray diphractogram was decreased the peak intensity and change crystalline form to amorphous form, while from IR spectrofotometer was a bit stretch compare with pure ketoconazole which indicate the formation of complex. Based on the results, concluded that the form of inclusion complex can increased dissolution rate from ketoconazole.